2017
DOI: 10.1186/s12896-017-0335-8
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin production in industrial strain Penicillium chrysogenum P2niaD18 is not dependent on the copy number of biosynthesis genes

Abstract: BackgroundMulti-copy gene integration into microbial genomes is a conventional tool for obtaining improved gene expression. For Penicillium chrysogenum, the fungal producer of the beta-lactam antibiotic penicillin, many production strains carry multiple copies of the penicillin biosynthesis gene cluster. This discovery led to the generally accepted view that high penicillin titers are the result of multiple copies of penicillin genes. Here we investigated strain P2niaD18, a production line that carries only tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 48 publications
(71 reference statements)
0
15
0
4
Order By: Relevance
“…This fits with the type of mutagenesis and artificial selection used for this process. Experimental work showed that tandem duplication of the pcbAB – pcbC – penDE cluster does not directly increase penicillin production over short time periods—a strain of P2niaD18 that was modified to lose one copy did not produce significantly less penicillin over a 96-h assay period 57 . Substantial copy number multiplication of the region among industrial strains still seems to implicate gene duplication in penicillin production, but perhaps only under specific growth conditions or over longer periods 18 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…This fits with the type of mutagenesis and artificial selection used for this process. Experimental work showed that tandem duplication of the pcbAB – pcbC – penDE cluster does not directly increase penicillin production over short time periods—a strain of P2niaD18 that was modified to lose one copy did not produce significantly less penicillin over a 96-h assay period 57 . Substantial copy number multiplication of the region among industrial strains still seems to implicate gene duplication in penicillin production, but perhaps only under specific growth conditions or over longer periods 18 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the industrial strain RutC 30 of Trichoderma reesei (used for enzyme production) is derived from a natural strain QM6A through repeated mutagenesis resulting in 15- to 20-fold improvement in cellulase biosynthesis (Peterson and Nevalainen, 2012). Another example is the enhancement of penicillin biosynthesis – it has been possible to enhance the titer by 85-fold through mutation (Ziemons et al, 2017). There are several such examples in industry, but only a few in microbes of agricultural importance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identification of new enzymes of this type might open new production routes. Interesting in this respect is the conversion of phenylacetonitrile to phenylacetic acid, which is used among others for the production of penicillin G (Ziemons et al 2017). The new insights obtained by identification and analysis of Nit09 contribute to the understanding of the sequence function relationship of arylacetonitrilases and thus to the development of better or novel nitrilase biocatalysts.…”
Section: A Novel and Stable Arylacetonitrilasementioning
confidence: 99%